Antiviral activity of the host defense peptide piscidin 1: investigating a membrane-mediated mode of action - Bepler, Tristan; Barrera, Michael D.; Rooney, Mary T.; Xiong, Yawei; Kuang, Huihui; Goodell, Evan; Goodwin, Matthew J.; Harbron, Elizabeth; Fu, Riqiang; Mihailescu, Mihaela; Narayanan, Aarthi; Cotten, Myriam L. (Frontiers in Chemistry, 2024)
Outbreaks of viral diseases are on the rise, fueling the search for antiviral therapeutics that act on a broad range of viruses while remaining safe to human host cells. In this research, we leverage the finding that the plasma membranes of host cells and the lipid bilayers surrounding enveloped viruses differ in lipid composition. We feature Piscidin 1 (P1), a cationic host defense peptide (HDP) that has antimicrobial effects and membrane activity associated with its N-terminal region where a cluster of aromatic residues and copper-binding motif reside. While few HDPs have demonstrated antiviral activity, P1 acts in the micromolar range against several enveloped viruses that vary in envelope lipid composition. Notably, it inhibits HIV-1, a virus that has an envelope enriched in cholesterol, a lipid associated with higher membrane order and stability. Here, we first document through plaque assays that P1 boasts strong activity against SARS-CoV-2, which has an envelope low in cholesterol. Second, we extend previous studies done with homogeneous bilayers and devise cholesterol-containing zwitterionic membranes that boast the liquid disordered (Ld; low in cholesterol) and ordered (Lo, rich in cholesterol) phases. Using dye leakage assays and cryo-electron microscopy on vesicles, we show that P1 has dramatic permeabilizing capability on the Lo/Ld, an effect matched by a strong ability to aggregate, fuse, and thin the membranes. Differential scanning calorimetry and NMR experiments demonstrate that P1 mixes the lipid content of vesicles and alters the stability of the Lo. Structural studies by NMR indicate that P1 interacts with the Lo/Ld by folding into an -helix that lies parallel to the membrane surface. Altogether, these results show that P1 is more disruptive to phase-separated than homogenous cholesterol-containing bilayers, suggesting an ability to target domain boundaries. Overall, this multi-faceted research highlights how a peptide that interacts strongly with membrane through an aromatic-rich N-terminal motif disrupt viral envelope mimics. This represents an important step towards the development of novel peptides with broad-spectrum antiviral activity.